Rhetorical Strategies in Digital Beauty Marketing Maybelline: A Stylistic Analysis - Nurhadi, Muizzu; Sabrina, Churiel Ain; Widodo, Alifia Nabila Putri (Universitas Negeri Gorontalo, 2023)
In the vibrant realm of digital beauty marketing, YouTube advertisements reign supreme. This study explores the rhetorical strategies used in Maybelline's YouTube ads to entice viewers and influence their purchasing decisions. Through a stylistic approach, it analyses five carefully selected advertisements from Maybelline lip-series products starring actress model Gigi Hadid that focus on grammatical and semantics levels of stylistics. The results of this study show that the use of hyperbole, visual imagery, kinesthetic imagery, and repetition are elements that are often used in Maybelline lip-series product advertising. The findings reveal a sophisticated use of language to persuade consumers to purchase Maybelline products. The findings underline the sophisticated use of language in digital beauty marketing employed by Maybelline to capture audience attention and promote their products. This shows that language style is important in the marketing industry in shaping consumer behavior in the field of beauty advertising.